Development of an Assertive Training Module to Prevent Bullying on Islamic Boarding School - Rahmawati, Novi Rosita; Khotimah, Husnul; Chusna, Alin Dewi; Thoriquttyas, Titis (Al-Hayat: Journal of Islamic Education, 2025)
This study aims to develop an assertiveness training module to prevent bullying in Islamic boarding schools, addressing the need for culturally relevant interventions. While existing programs offer general social skills training, few are tailored to the unique environment of pondok pesantren. The Research and Development (R&D) method was chosen for this study. This study followed the Borg & Gall development model modified and simplified from ten to seven steps. Data were collected using a validation questionnaire assessed by material experts, media experts, and prospective users (Musyrifah). The results of the study showed that the assertive training module was declared feasible in terms of content and media based on validation by media experts (77%) and materials (71%), with a score of the category "feasible." In the next step, a limited field trial involving seven participants resulted in 81.78%, categorized as "Very Feasible." These results indicate that the module is acceptable and relevant to the intended educational environment. A small trial group, typical of developing-country contexts, limited the study. Further large-scale testing is recommended. This study presents an innovative, context-specific tool for bullying prevention in Islamic boarding schools. It contributes to the limited literature on culturally tailored educational interventions and offers a foundation for future development and wider application.